2012
DOI: 10.1158/0008-5472.can-11-3317
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte–Stellate Cell Cross-Talk in the Liver Engenders a Permissive Inflammatory Microenvironment That Drives Progression in Hepatocellular Carcinoma

Abstract: Many solid malignant tumors arise on a background of inflamed and/or fibrotic tissues, features which are found in more than 80% hepatocellular carcinomas (HCC). Activated hepatic stellate cells (HSC) play a critical role in fibrogenesis associated with HCC onset and progression, yet their functional impact on hepatocyte fate remains largely unexplored. Here, we used a coculture model to investigate the crosstalk between hepatocytes (human hepatoma cells) and activated human HSC. Unsupervised genome-wide expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
191
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 43 publications
9
191
0
3
Order By: Relevance
“…Several studies have shown that activated HSCs may also contribute to liver carcinogenesis, owing to their capacity to generate a permissive environment that facilitates liver tumor cell growth. Coculture experiments have demonstrated that activated HSCs promote migration, growth, invasion, and survival of hepatocarcinoma and cholangiocarcinoma cells (11,13). In addition, hepatic myofibroblasts secrete proinflammatory and proangiogenic factors essential for tumor growth, and in parallel inhibit immune surveillance by natural killer (NK) and natural killer T (NKT) cells (13,53,97).…”
Section: Contribution Of Hepatic Myofibroblasts To Liver Regenerationmentioning
confidence: 99%
“…Several studies have shown that activated HSCs may also contribute to liver carcinogenesis, owing to their capacity to generate a permissive environment that facilitates liver tumor cell growth. Coculture experiments have demonstrated that activated HSCs promote migration, growth, invasion, and survival of hepatocarcinoma and cholangiocarcinoma cells (11,13). In addition, hepatic myofibroblasts secrete proinflammatory and proangiogenic factors essential for tumor growth, and in parallel inhibit immune surveillance by natural killer (NK) and natural killer T (NKT) cells (13,53,97).…”
Section: Contribution Of Hepatic Myofibroblasts To Liver Regenerationmentioning
confidence: 99%
“…This choice was based on previous published evidence indicating that activated HSC produce and secrete soluble factors and chemokines that promote a pro-inflammatory microenvironment, tissue angiogenesis and tumour progression. Therefore, activated hHSC favour the ''homing'' of tumour cells in the liver microenvironment [20][21][22]. Hence, the conditioned medium of activated hHSC is as an excellent and specific tool to investigate the possible cross-talk between cancer cells and hHSC during chemotaxis.…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…Hepatocellular injury followed by inflammation and activation of the innate immune system may lead to early-stage liver fibrosis, resulting in hepatic stellate cell (HSC) activation and extracellular matrix (ECM) deposition (12). Gene expression analyses also highlighted the role of proinflammatory cytokines (e.g., IL-1␤ and IL-6) and chemokines (e.g., IL-8 and CCL2) as key orchestrators of the cross talk between hepatocytes and activated HSCs (13). The invasive capacity of malignant cells increases in the presence of IL-1␤ and IL-6 (14).…”
mentioning
confidence: 99%